Analysis of the Impact of Online Loan Usage from the Perspective of Islamic Economics (Case Study on Students of Jambi University) - Alreza, Muhammad; Enggrani Fitri, Lucky; , Ridhwan (Bertuah Jurnal Syariah dan Ekonomi Islam, 2025)
This study aims to analyze the factors and impacts of online loans from the perspective of Islamic economics. The research was conducted by analyzing primary data obtained through interviews with informants and presented using data reduction techniques. This is a qualitative study. The results show that there are both positive and negative findings regarding online loans from the perspective of Islamic economics.